Repatrierea forței de muncă în contextul pandemiei COVID-19 - Mălina Voicu; Alexandra Deliu; Simona Stănescu; Elena Spiridon (Sociologie Românească, 2023)
This article aims at providing information about Romanian emigrants in terms of destinations and integration on the labour market at the destination and, at the same time, at tackling with the effects of the COVID-19 pandemic on the mobility and eventual return of Romanian emigrants. For these explorations, we use quantitative data from various sources. The Repatriation of the Work Force is a research conducted in 2020, in which the local authorities from 3,181 administrative units in Romania were contacted and asked a series of questions regarding, among other topics, migration from and return migration to their locality. 742 answers were obtained, which were complemented with statistical information from Eurostat – Romanian citizens residing abroad, and the Romanian Border Police – traffic in an out Romanian borders since the beginning of the pandemic, compared to similar periods in 2019. The data provides an image of Romanian migrants abroad that is in line with what previous studies show, in terms of favourite destinations (Italy, Spain, Germany, Great Britain) and occupations at the destination (constructions, agriculture, housekeeping). Data from the Romanian Border Police show that return to Romania had some spikes in 2020, and suggests circularity and complex mobility trajectories.